'Don't look away': Help your child learn empathy from news of separated children. Issue 11 (9th October 2019) - Knopf, Alison
Abstract : The tragedy of the immigrant children who have been separated from their parents is too intense to "teach" to young children. "Don't look away" was a frequent theme when the stories, pictures, and videos started coming out showing children who were separated from their parents. Even adults couldn't take it.